2009
DOI: 10.1080/03009740802360632
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with leflunomide and methotrexate for patients with active rheumatoid arthritis

Abstract: THE combination of leflunomide and methotrexate was effective and well tolerated in the treatment of active RA patients. This combination may be a useful option as an initial treatment for active RA before starting biological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
9
1
2
Order By: Relevance
“…Administration of both MTX and LEF to rats with type II collagen-induced arthritis reduced serum levels of IL-17, receptor activator of NF-kB ligand (RANKL), and osteoprotegerin (OPG)37. Large cohort studies indicate that combination therapy with MTX and LEF is efficacious and safe in the treatment of active RA383940, and provides superior clinical benefits to MTX alone39. Therefore, we applied MTX and LEF combination therapy in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of both MTX and LEF to rats with type II collagen-induced arthritis reduced serum levels of IL-17, receptor activator of NF-kB ligand (RANKL), and osteoprotegerin (OPG)37. Large cohort studies indicate that combination therapy with MTX and LEF is efficacious and safe in the treatment of active RA383940, and provides superior clinical benefits to MTX alone39. Therefore, we applied MTX and LEF combination therapy in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that combinations of DMARDs are more effective than monotherapy. 14,15,16 In addition, biological agents are more effective when combined with DMARDs, in particular methotrexate. 17,18,19 This justifies the strategy of combining DMARDs or biological agents found in most patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…В конце 1990-х -начале 2000-х гг. такая комбинация была достаточно широко распространена и продемон-стрировала достаточно отчетливый дополнительный положительный эффект по сравнению с монотерапией метотрексатом [70][71][72][73][74]. В то же время вероятность раз-вития нежелательных реакций (НР) на фоне такой комби-нации оказалась также существенно выше, чем при моно-терапии каждым из препаратов [75][76][77], что ограничивает применение этой комбинации на практике.…”
Section: таблица результаты основных исследований эффективности лефлunclassified